Interactive animated e-books - A. Sayed, Asma; K. A. AlAllan, Yousef; Jahameh, Safaa; M. Mustafa, Hadeel; Nayef Al Tarawneh, Hassan (project baikal, 2025)
Books are one of the oldest inventions of mankind. Today, a growing number of people on Earth no longer read and show signs of ‘functional illiteracy’. New techniques and technologies are required to convey complex, deep and emotionally coloured images to the reader of books. It is such images that form a significant part of teaching the history and theory of architecture. The article deals with the project of an electronic multimedia animated book (textbook) devoted to the philosophy and history of the Arabic style in architecture.